ARE OPOSSUMS CAPABLE of TRANSMITTING LEPTOSPIROSIS IN URBAN AREAS? - Lucheis, S. B. (2009)
APTA, Unidade Pesquisa Bauru, Polo Ctr Oeste, Dept Descentralizacao Desenvolvimento, BR-17030000 Bauru, SP, Brazil